EFEITOS DO MANEJO DE HOVENIA DULCIS THUNB. SOBRE A COMPOSIÇÃO, ESTRUTURA, DIVERSIDADE E DINÂMICA DA REGENERAÇÃO NATURAL EM FLORESTA OMBRÓFILA MISTA MONTANA - GRESPAN, TIAGO (2022)
The general objective of this thesis was to evaluate in Mixed Ombrophylous Forest the effect of selective cuttings of the invasive alien species H. dulcis about the regeneration natural, from the comparison between areas with and without management of individuals adults of H. dulcis, seeking to understand the ecological processes underlying factors, in order to subsidize strategies for their management. They were selected six fragments of Montane Mixed Ombrophylous Forest in stage medium to advanced succession, with occurrence of the species, located in private rural properties in the municipality of Fernandes Pinheiro, Paraná. Among the six selected fragments, three were managed and the other three were used as witnesses. The H. dulcis management proposal was designed with two main objectives: the control of the species as a way of maintaining the balance of native forest fragments; the aggregation and diversification of the rural producer's source of income, through the commercialization of logs. The cutting intensity of the exotic species was defined, mainly, a partir da dinâmica entre a entrada e saída dos indivíduos. As a result, it was verified that the tree component presented predominance of species belonging to the demanding climatic ecological group of light and pioneers, associated with the low presence of species belonging to the shade-tolerant climate group, situando-se em fase de estruturação da comunidade, demonstrando susceptibilidade à invasão de H. dulcis. To the natural regeneration of the species H. dulcis below 0.3 m in height was not direct relationship between abundance of regenerants and canopy openness was verified. On the other hand, opening levels considered intermediate for this study, ranging from 10 to 20%, demonstrated more favorable conditions for the seed germination and seedling emergence. There was a relationship inverse between accumulated litter and the number of individuals regenerating the H. dulcis species, as well as a positive relationship between higher average heights and larger canopy openings. Annual death rates between periods from 2019 to 2021 were higher in areas with smaller canopy openings and with higher values ​​of accumulated litter. Analyzing the regeneration above 0.3 m in height over a two-year period, it was found that the management of tree individuals of the species H. dulcis generated alteration in the floristic composition in places with intervention, characterized by the increase of species, and their abundance, belonging to the pioneer ecological group, typical of early stages of succession. There was a reduction in diversity of the Shannon and Simpson indices in the managed environments. Higher rates of mortality were observed in managed areas, and these effects associated with extraction trails; injuries caused by the overthrow of tree individuals over the remaining individuals; just like the competition between individuals occupying newly disturbed areas. At the same time, higher recruitment rates were observed for areas managed, influenced by the ecophysiological responses of the species present in the areas to the openings of clearings, in the form of a seedling bank or of dormant seeds in the soil and, or, of remaining individuals, as well as well as post-disturbance migrant species via the dispersal process of surrounding vegetation. The analysis of indicator species, together with the non-metric multidimensional scaling analysis, allowed to identify that, in addition to the species H. dulcis, the species Solanum mauritianum, Vassobia breviflora, Solanum paranense, Cestrum intermedium and Araucaria angustifolia were favored by the interventions. Through the redundancy analysis, it was possible to verify the effect of space in the structuring of natural regeneration, associated in this research with neutral processes of population or dynamics of communities, characterized by the effects of the temporal structure produced by the species' own groupings, generating autocorrelation in the response variables (species); as well as environmental variables, in this case, associated with hydromorphic soils, favoring species such as Annona emarginata, Campomanesia xanthocarpa and Sebastiania brasiliensis. still, the analysis allowed us to identify that the management, associated with the size of the individuals removed, together with the pressure of propagules of the H. dulcis species, favored the invasion process.